2018
DOI: 10.3390/socsci7030033
|View full text |Cite
|
Sign up to set email alerts
|

Can Social Capital influence Smallholder Farmers’ Climate-Change Adaptation Decisions? Evidence from Three Semi-Arid Communities in Burkina Faso, West Africa

Abstract: This study examines the influence of farmers' social capital on their decisions to deal with climate change and climate variability in Burkina Faso. The study is based on a household survey conducted among 450 households, randomly selected from three communities in Burkina Faso. Two indexes were constructed to capture farmers' structural and cognitive social capital; and using generalized Poisson regression (GPR) and a multivariate probit model, the study probes the effect of farmers' social capital on their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 30 publications
(27 reference statements)
1
18
1
1
Order By: Relevance
“…On the other hand, various types of (bridging) social capital can improve the information flow between a farm household and a formal lender [41]. Formal credit is rationed, and not everyone can get a loan from a formal financial institution because of the asymmetric nature of information between the bank and the borrower [1].…”
Section: The Effect Of Two Kinds Of Social Capital On Farm Household'mentioning
confidence: 99%
“…On the other hand, various types of (bridging) social capital can improve the information flow between a farm household and a formal lender [41]. Formal credit is rationed, and not everyone can get a loan from a formal financial institution because of the asymmetric nature of information between the bank and the borrower [1].…”
Section: The Effect Of Two Kinds Of Social Capital On Farm Household'mentioning
confidence: 99%
“…Farmers' social networks (farmers' groups and others social organisations) can play a crucial role in farmers' decision-making, through mechanisms such as information diffusion, knowledge sharing, cooperation, solidarity and social interaction [22,23]. A common feature of small-scale farmers is their low participation in the markets due of a range of constraints and barriers such as poor transport and storage infrastructures, weak banking system (lack of credit and insurance markets), non-competitive situations and inadequate market information.…”
Section: Introductionmentioning
confidence: 99%
“…Although various studies have found social influence to positively affect adoption (Katungi, 2006;Mashavave et al, 2013;Yamé ogo, William, Fonta, & Wünscher, 2018) the study found mixed, but not statistically significant relationships between social influence and adoption of CA principles. The findings are supported by Talukder and Quazi (2011) and Hulst and Posthumus (2016), who found no social influence or peer pressure effects on adoption.…”
Section: The Role Of the Social System (Social Influence By Laws Cumentioning
confidence: 83%